CPEB4 modulates liver cancer progression by translationally regulating hepcidin expression and sensitivity to ferroptosis - M. Eugenia Delgado; Salvador Naranjo-Suarez; Marta Ramírez-Pedraza; Beatriz I. Cárdenas; Carmen Gallardo-Martínez; Alexandra Balvey; Eulalia Belloc; Judit Martín; Mark Boyle; Raúl Méndez; Mercedes Fernandez (JHEP Reports)
Background & Aims: Liver cancer is a significant global health issue, with its incidence rising in parallel with the obesity epidemic. The limited therapeutic options available emphasize the need for a better understanding of the molecular pathways involved in its pathogenesis. While much of the previous research has focused on transcriptional changes, this study examines translational alterations, specifically the role of cytoplasmic polyadenylation element binding protein 4 (CPEB4), a key regulator of translation. Methods: We analyzed publicly available patient databases and conducted studies using human and mouse liver cancer cells, xenograft and allograft models, mouse models of high-fat diet-related liver cancer, and CPEB4 knockout and knockdown mice and cell lines. Results: Patient data analysis (n = 87) showed a strong correlation between low CPEB4 levels and reduced survival rates (p <0.001). In mouse models of diet-induced liver cancer (n = 10–15 per group), both systemic and hepatocyte-specific CPEB4 knockout mice exhibited significantly increased tumor burden compared with wild-type controls (p <0.05). In vitro studies using human and murine liver cancer cells (n = 3 biological replicates) demonstrated reduced sensitivity to ferroptosis upon CPEB4 depletion when induced by erastin or RSL3 (p <0.01). Mechanistically, CPEB4 deficiency suppressed hepcidin expression, leading to elevated ferroportin levels, decreased intracellular iron accumulation, and reduced lipid peroxidation (p <0.05). Conclusions: This study uncovers a novel CPEB4-dependent mechanism linking translational control to liver cancer progression and ferroptosis regulation. Therapeutic strategies targeting CPEB4-mediated pathways hold promise for advancing treatment options in liver cancer. Impact and implications:: This study addresses the pressing need for improved therapies in liver cancer, particularly given its increasing prevalence linked to obesity and metabolic-associated fatty liver disease. By uncovering the role of the RNA-binding protein cytoplasmic polyadenylation element binding protein 4 (CPEB4) in modulating iron regulation and cancer cell sensitivity to ferroptosis, our research highlights a new translational mechanism with potential therapeutic relevance. These findings are particularly significant for clinicians, researchers, and policymakers focused on advancing targeted treatments for hepatocellular carcinoma. If further validated in human clinical studies, targeting CPEB4-mediated pathways could help develop treatments that enhance cancer cell susceptibility to ferroptosis, offering a promising strategy for improving outcomes in patients with advanced liver cancer. Limitations of the study include the need for further clinical validation to confirm these preclinical findings in human disease contexts.